Antibody–drug conjugates: Recent advances in linker chemistry - Su, Zheng; Xiao, Dian; Xie, Fei; Liu, Lianqi; Wang, Yanming; Fan, Shiyong; Zhou, Xinbo; Li, Song (Acta pharmaceutica Sinica. B, 2021)
Antibody–drug conjugates (ADCs) are gradually revolutionizing clinical cancer therapy. The antibody–drug conjugate linker molecule determines both the efficacy and the adverse effects, and so has a major influence on the fate of ADCs. An ideal linker should be stable in the circulatory system and release the cytotoxic payload specifically in the tumor. However, existing linkers often release payloads nonspecifically and inevitably lead to off-target toxicity. This defect is becoming an increasingly important factor that restricts the development of ADCs. The pursuit of ADCs with optimal therapeutic windows has resulted in remarkable progress in the discovery and development of novel linkers. The present review summarizes the advance of the chemical trigger, linker‒antibody attachment and linker‒payload attachment over the last 5 years, and describes the ADMET properties of ADCs. This work also helps clarify future developmental directions for the linkers. Antibody–drug conjugates (ADCs) are revolutionizing cancer therapy. Linkers, determining both efficacy and off-target toxicity, are the core components of ADCs. The advances of linkers over the past 5 years are reviewed. [Display omitted]